PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB PADA MATA PELAJARAN PEMASANGAN DAN KONFIGURASI PERANGKAT JARINGAN DI SMK N 2 PADANG - Insani, Yumara; Novita, Rini; Junaidi, Satrio (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The goal of this project is to create reliable and useful web-based instructional materials for SMK Negeri 2 Padang's Network Device Installation and Configuration course.  The poor level of student comprehension brought on by the usage of less interactive media and the inefficiency of traditional teaching techniques are the issues.  The five steps of the ADDIE model analysis, design, development, implementation, and evaluation are used in this study's Research and Development (RD) methodology.  With a media validity test score of 0.81 (valid category) and a material validity test score of 0.81 (valid category), the study's findings show that the web-based learning materials created have a high degree of validity.  Furthermore, the practicality test findings indicate that this media is highly practical, with 81.94% of teachers and 82% of students using it for practice.  These findings support the validity and applicability of this web-based learning resource for educational purposes.  It is anticipated that using this media will improve learning outcomes and facilitate students' interactive comprehension of difficult subjects.